Prevalence and intensity of soil-transmitted helminth infections of children in sub-Saharan Africa, 2000–18: a geospatial analysis. Issue 1 (January 2021) - Sartorius, Benn; Cano, Jorge; Simpson, Hope; Tusting, Lucy S; Marczak, Laurie B; Miller-Petrie, Molly K; Kinvi, Boniface; Zoure, Honorat; Mwinzi, Pauline; Hay, Simon I; Rebollo, Maria; Pullan, Rachel L
Summary: Background: Driven by global targets to eliminate soil-transmitted helminths as a public health problem, governments have rapidly rolled out control programmes using school and community-based platforms. To justify and target ongoing investment, quantification of impact and identification of remaining high-risk areas are needed. We aimed to assess regional progress towards these targets. Methods: We did a continental-scale ecological analysis using a Bayesian space–time hierarchical model to estimate the effects of known environmental, socioeconomic, and control-related factors on the prevalence of soil-transmitted helminths, and we mapped the probability that implementation units had achieved moderate-to-heavy intensity infection prevalence of less than 2% among children aged 5–14 years between Jan 1, 2000, and Dec 31, 2018. Findings: We incorporated data from 26 304 georeferenced surveys, spanning 3096 (60%) of the 5183 programmatic implementation units. Our findings suggest a reduction in the prevalence of soil-transmitted helminths in children aged 5–14 years in sub-Saharan Africa, from 44% in 2000 to 13% in 2018, driven by sustained delivery of preventive chemotherapy, improved sanitation, and economic development. Nevertheless, 1301 (25%) of 5183 implementation units still had an estimated prevalence of moderate-to-heavy intensity infection exceeding the 2% target threshold in 2018, largely concentrated in nine countries (in 1026 [79%] of 1301 implementation units): Nigeria, Democratic Republic of the Congo, Ethiopia, Cameroon, Angola, Mozambique, Madagascar, Equatorial Guinea, and Gabon. Interpretation: Our estimates highlight the areas to target and strengthen interventions, and the areas where data gaps remain. If elimination of soil-transmitted helminths as a public health problem is to be achieved in sub-Saharan Africa by 2030, continued investment in treatment and prevention activities are essential to ensure that no areas are left behind. Funding: Bill & Melinda Gates Foundation.